Analysis of Factors Strengthening Human Capital Competitiveness in Indonesia’s Industry through Workplace Learning Model based on Indonesian Qualification Framework - Wardhana, Mada Aditia; Lestari, Endah; Nikmah, Musilatin (Universitas Pendidikan Nasional, 2025)
Strengthening workforce competitiveness in Indonesia requires workplace learning aligned with the Indonesian Qualifications Framework. This study aimed to identify and validate the latent structure of IQF based workplace learning and to outline an evaluation instrument and policy levers. We conducted an online cross-sectional survey of 400 workers across all provinces and applied exploratory factor analysis with polychoric correlations, oblimin rotation, parallel analysis, and a scree examination, complemented by content analysis of an open-ended question. Sampling adequacy was excellent with KMO 0.96 and Bartlett significance p under 0.001. Four coherent dimensions emerged that together explained about 65 percent of variance. Structured Competency Development captured structured training, standards, research, human resource planning, and certification. Performance Management and Workload gathered assignment, workload, remuneration, performance, and knowledge sharing. Experience Based Learning covered mentoring, internship, coaching, and job rotation. Educational Qualifications was defined chiefly by education level. Model fit was strong with RMSR 0.03 and moderate inter factor correlations, and qualitative keywords on work, skills, and experience converged with these factors. The study contributes a theoretically integrated IQF aligned model and a ready blueprint for measurement and auditing. Practically it informs policy and industry programs that link training with research and technology, formalise mentoring, reward knowledge sharing in performance systems, and map careers to qualification levels, and the instrument can audit learning ecosystems and guide resource allocation across priority sectors.